2020
DOI: 10.1101/2020.04.14.040766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha-satellite RNA transcripts are repressed by centromere-nucleolus associations

Abstract: Centromeres play a fundamental role in chromosome segregation. Although originally thought to be silent chromosomal regions, centromeres are actively transcribed.However, the behavior and contributions of centromere-derived RNAs have remained unclear. Here, we used single-molecule fluorescence in-situ hybridization (smFISH) to detect alpha-satellite RNA transcripts in intact human cells. We find that alpha-satellite RNA smFISH foci fluctuate in their levels over the cell cycle and do not remain associated with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Rather, the rapid appearance of damage during progression through mitosis after acute depletion of Ki-67 (Figure 3) leads us to favor the idea that Ki-67 directly protects mitotic chromosomes. In this view, the appearance of γH2AX is one more aspect of defective chromatin maintenance upon Ki-67 depletion, consistent with previously described structural deformations of heterochromatin (11), loss of association and modification of heterochromatin at the nucleolar periphery (10–13), and reduced transcriptional silencing of pericentromeric alpha-satellite repeats (50).…”
Section: Discussionsupporting
confidence: 91%
“…Rather, the rapid appearance of damage during progression through mitosis after acute depletion of Ki-67 (Figure 3) leads us to favor the idea that Ki-67 directly protects mitotic chromosomes. In this view, the appearance of γH2AX is one more aspect of defective chromatin maintenance upon Ki-67 depletion, consistent with previously described structural deformations of heterochromatin (11), loss of association and modification of heterochromatin at the nucleolar periphery (10–13), and reduced transcriptional silencing of pericentromeric alpha-satellite repeats (50).…”
Section: Discussionsupporting
confidence: 91%
“…R-loops, which form co-transcriptionally, are prevalent at replication-transcription conflicts (38,40). Centromeres are actively transcribed throughout the cell cycle (17,41), raising the hypothesis that CENP-A depletion causes R-loop formation due to convergence of replication and transcription machineries. Upon release from thymidine-mediated arrest, CENP-A depletion did not affect the levels of centromere transcripts during early S-phase, but when cells progressed to late S-phase, the RNA levels increased ( Figure 3F).…”
Section: Resultsmentioning
confidence: 99%
“…As CENP-A levels are reduced in senescent cells 59 (41) and favorize rearrangements at acrocentric chromosomes. During neocentromere formation, CENP-A can also be lost from the original alpha-satellite locus which has been reported to lead to centromere erosion at the repeats (64).…”
Section: Discussionmentioning
confidence: 98%
“…Recent work showed that knock-down of CENP-C resulted in increased centromeric transcription [ 117 ], whereas knock-down of centromeric transcripts resulted in increased levels of centromeric CENP-C [ 31 ]. These data suggest that there is a functional interaction between CENP-C and centromeric transcription.…”
Section: Functions Of Centromeric Transcriptionmentioning
confidence: 99%